Integrated Model Considering Effects of Zero Injection Buses and Conventional Measurements on Optimal PMU Placement - Khajeh, Kiarash Gharani; Bashar, Erfan; Rad, Ali Mahboub; Gharehpetian, Gevork B. (IEEE transactions on smart grid, 2017)
The main requirements of the wide-area monitoring system is to acquire the real-time measurement of state variables that can be provided by phasor measurement units (PMUs). The optimal PMU placement is the leading object of this paper, which is presented as an integer linear programming problem. The zero injection buses (ZIBs) and conventional measurements (CMs) enhance the system observability. In this paper, a novel integrated model is presented to consider the effects of the ZIBs and CMs for PMU placement. The proposed model considers limitations caused by ZIBs and CMs that have not been studied earlier. The single branch and single PMU outage, as two common contingencies, are also separately and simultaneously taken into account. The proposed method is applied to five different IEEE test systems (14, 30, 39, 57, and 118 bus) in order to demonstrate its effectiveness. The obtained results are compared with that of the other studies.